The Survival and Continuity of Islamic Boarding School in the Era of Changes - Royani, Ahmad; Hepni (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The fast change requires the ability of Islamic boarding schools to respond fast, rightly, and adaptively. Using qualitative phenomenology, this study tries to see the changes faced by the Islamic Boarding School of Nurul Islam Jember. The result of this study is that the adaptation of changes is made by the model of safeguarding and conserving the positive local values (localities) and is helpful for the Islamic boarding school. As an agent of change, the Islamic boarding school of Nurul Islam participates in society’s change actively. Besides that, the canceling of personality is to prepare santri to have the religious and nonreligion knowledge to be an Islamic human who can apply their knowledge. The personality built by the Islamic boarding school of Nurul Islam can face and respond to the changes without ignoring morals (Akhlaq). The Islamic boarding school of Nurul Islam tries to integrate the formal and Islamic boarding school systems to build capable generations. The Islamic boarding school with soft skills and the formal school with life skills will be the solution to adaptive education in the era of changes.